Epidemiology and clinical analysis of critical patients with child maltreatment admitted to the intensive care units. Issue 23 (June 2017) - Lee, En-Pei; Hsia, Shao-Hsuan; Huang, Jing-Long; Lin, Jainn-Jim; Chan, Oi-Wa; Lin, Chia-Ying; Lin, Kuang-Lin; Chang, Yu-Ching; Chou, I-Jun; Lo, Fu-Song; Lee, Jung; Hsin, Yi-Chen; et al.
Abstract : Abstract: Children with abuse who are admitted to the intensive care unit (ICU) may have high mortality and morbidity and commonly require critical care immediately. It is important to understand the epidemiology and clinical characteristics of these critical cases of child maltreatment. We retrospectively evaluated the data for 355 children with maltreatments admitted to the ICU between 2001 and 2015. Clinical factors were analyzed and compared between the abuse and the neglect groups, including age, gender, season of admission, identifying settings, injury severity score (ISS), etiologies, length of stay (LOS) in the ICU, clinical outcomes, and mortality. In addition, neurologic assessments were conducted with the Pediatric Cerebral Performance Category (PCPC) scale. The most common type of child maltreatments was neglect (n = 259), followed by physical abuse (n = 96). The mean age of the abuse group was less than that of the neglect group ( P < .05). Infants accounted for the majority of the abuse group, and the most common etiology of abuse was injury of the central nervous system (CNS). In the neglect group, most were of the preschool age and the most common etiologies of abuse were injury of the CNS and musculoskeletal system ( P < .001). The mortality rate in the ICU was 9.86%. The ISS was significantly associated with mortality in both the 2 groups (both P < .05), whereas the LOS in the ICU and injuries of the CNS, musculoskeletal system, and respiratory system were all associated with mortality in the neglect group (all P < .05). The PCPC scale showed poor prognosis in the abuse group as compared to the neglect group ( P < .01). In the ICU, children in the abuse group had younger age, higher ISS, and worse neurologic outcome than those in the neglect group. The ISS was a predictor for mortality in the abuse and neglect groups but the LOS in the ICUs, injuries of the CNS, musculoskeletal system, and respiratory system were indicators for mortality in the neglect group. Most importantly, identifying the epidemiological information may provide further strategies to reduce the harm, lower the medical costs, and improve clinical care quality and outcomes in children with abuse.